2017
DOI: 10.3892/mmr.2017.6955
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of gut microbiota in the association between gastrointestinal motility and 5-HT expression/M2 macrophage abundance in the gastrointestinal tract

Abstract: Serotonin (5‑hydroxytryptamine; 5‑HT) may be a key player in gastrointestinal (GI) motility and the GI immune system. In the present study, the effect of gut microbiota on the association between GI motility, and 5‑HT expression and macrophage abundance in the GI tract was examined. Germ‑free (GF) mice (6 weeks old) were orally administered a fecal bacterial suspension prepared from specific pathogen‑free mice and their GI tissues were evaluated 4 weeks later. The expression of 5‑HT and mannose receptor (MR) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 24 publications
1
25
1
Order By: Relevance
“…These findings are seemingly at odds with a previous study reporting that development of CD169 + colon MPs is independent of microbiota, 15 however, this study examined antibiotic-treated, but not GF mice, which are different both immunologically and metabolically. 48,49 Furthermore, consistent with our results showing that GF mice conventionalized by co-housing with SPF mice for 6 weeks recovered this cell population from the colon, a prior study demonstrated that fecal transplants into GF mice resulted in an increase in CD206-expressing cells in the muscularis layer of colon and small intestine, 25 indicating a commensal microbiotadependent mechanism promotes their development.…”
Section: Developmental Bifurcation Of Colon Mps Is Controlled By Uniqsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are seemingly at odds with a previous study reporting that development of CD169 + colon MPs is independent of microbiota, 15 however, this study examined antibiotic-treated, but not GF mice, which are different both immunologically and metabolically. 48,49 Furthermore, consistent with our results showing that GF mice conventionalized by co-housing with SPF mice for 6 weeks recovered this cell population from the colon, a prior study demonstrated that fecal transplants into GF mice resulted in an increase in CD206-expressing cells in the muscularis layer of colon and small intestine, 25 indicating a commensal microbiotadependent mechanism promotes their development.…”
Section: Developmental Bifurcation Of Colon Mps Is Controlled By Uniqsupporting
confidence: 89%
“…23,24 CX3CR1 hi colon MPs during colitis appear to largely maintain their regulatory phenotype, 23 however the origin of these regulatory MPs during colitis is still unclear. 5,8,23 A role for the commensal microbiota has been implicated in colon MP differentiation and/or maintenance in several studies, with lower numbers of both monocyte-derived and tissue-resident long-lived MPs present in germ-free (GF) mice, 5,6,12,25,26 however, a substantial number of mature colon MPs are still found in adult GF mice. 5,6,12 In addition, it was recently shown that antibiotic exposure causes intestinal MPs to become hyper-responsive to bacterial exposure, resulting in enhanced cytokine production and long-term enhanced Th1 responses and dysbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…160,162 Supporting these findings, we have clarified that 5-HT expression is increased in the colon of GF mice after fecal transplantation, and that moreover M2 macrophages in the colonic muscular layer are increased in those mice. 163 Furthermore, it is noteworthy that the numbers of muscularis M2 macrophages and 5-HT-positive endocrine cells are significantly correlated throughout the GI tract, and that their increase is associated with acceleration of GI motility. Thus, the gut microbiota plays a role in the association between accelerated GI motility and induction of the 5 HT/muscularis mannose receptor positive macrophage axis in the GI tract.…”
Section: Gut Microbiota Immune System Activation and Gastrointestinmentioning
confidence: 97%
“…Thus, the gut microbiota plays a role in the association between accelerated GI motility and induction of the 5 HT/muscularis mannose receptor positive macrophage axis in the GI tract. 163 Specifically, Muller et al 164 have demonstrated that M2 macrophages migrating adjacent to the ENS may be involved in the control of GI motility through cross-talk with enteric neurons via bone morphogenetic protein 2 signaling.…”
Section: Gut Microbiota Immune System Activation and Gastrointestinmentioning
confidence: 99%
“…Alternatively, steel beads and barium are used in non‐terminal experiments, alongside fluoroscopic video recordings, to record the active transit of the beads over time 4 . Whole gut transit, however, is most commonly evaluated by the oral administration of a non‐absorbable marker such as carmine red and monitoring the first appearance of the stool 5‐10 . This process, however, is time consuming and does not rely on unbiased judgment of the first appearance of the transit marker.…”
Section: Introductionmentioning
confidence: 99%